2022
DOI: 10.1371/journal.pone.0265758
|View full text |Cite
|
Sign up to set email alerts
|

Association between hematocrit and the 30-day mortality of patients with sepsis: A retrospective analysis based on the large-scale clinical database MIMIC-IV

Abstract: This research sought to ascertain the relationship between hematocrit (HCT) and mortality in patients with sepsis. Methods: A retrospective analysis was conducted on the clinical data of septic patients who were hospitalized between 2008 and 2019 in an advanced academic medical center in Boston, Massachusetts, registered in the Medical Information Mart for Intensive Care IV (MIMIC-IV) database, We analyzed basic information including gender, age, race, and types of the first admission, laboratory indicators in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Hemodilution can occur in patients who are edematous, hypervolemic, or who appear to be euvolemic on clinical examination [24]. A low hematocrit, especially when compounded with true anemia, results in higher mortality in patients with congestive heart failure [24] and sepsis [25]. In our case, a normal hematocrit level is associated with a protective factor of severe CAP.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Hemodilution can occur in patients who are edematous, hypervolemic, or who appear to be euvolemic on clinical examination [24]. A low hematocrit, especially when compounded with true anemia, results in higher mortality in patients with congestive heart failure [24] and sepsis [25]. In our case, a normal hematocrit level is associated with a protective factor of severe CAP.…”
Section: Discussionmentioning
confidence: 54%
“…Anemia has been found to increase children's susceptibility to contracting pneumonia [27] and increases the risk of death [18,28]. Although the biomolecular mechanism for a low hematocrit level contributing to increased death has yet to be fully elucidated, some theories exist [25]. Acute systemic infections cause inflammatory responses, which reduce the number of red blood cells entering circulation dramatically [29].…”
Section: Discussionmentioning
confidence: 99%
“…Analyte-specific validation for Hct effect is particularly important because Hct levels can vary significantly among individuals and even within individuals at different times. 66 The accuracy and precision of glutathione and glutathione disulphide measurements using this approach were comparable to those of conventional liquid-blood analyses. However, technological advances are application-specific and must be validated to ensure comparable outcomes to conventional approaches.…”
Section: Sub-classificationmentioning
confidence: 73%
“…A recent research, however, discovered that fever alone did not consistently distinguish juvenile CAP from other respiratory infections [15,16]. A previous investigation reported that temperature of 39 °C was associated with pediatric pneumonia mortality at an adjusted risk ratio of 1.9 [17]. Furthermore, the length of illness, particularly fever, has been linked to a poor prognosis in children with pneumonia [18,19].…”
Section: Resultsmentioning
confidence: 98%